Using Macro-Invertebrates as Bio-indicators to Assess Water Quality in Selected Water Bodies of Xuan Son National Park, Phu Tho Province - Son, Nguyen Thanh; Quynh, Nguyen Xuan; Vinh, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: The present study aims to assess environmental condition of selected water bodies in Xuan Son National Park, Phú Thọ province. Field surveys in 2015 have yielded 60 macro-invertebrate families that were included in the BMWP VIET scoring system, which were collected from 19 sampling sites. The ASPT scores showed that the water quality in 13 of those sampling sites were fairly clean (Oligosaprobe) with values ranging from 6.0 - 6.5. The remaining six sampling sites had ASPT scores ranging from 5.5 - 5.9, corresponding to quite polluted level (b-Mesosaprobe). In general, the water quality of water bodies in Xuan Son NP is still safe for aquatic organisms’ lives. Keywords: Macro-invertebrates, bio-indicators, BMWP, ASPT, Xuan Son National park.